ALDOC promotes neuroblastoma progression and modulates sensitivity to chemotherapy drugs by enhancing aerobic glycolysis - Chen, Yunpeng; Zhu, Haixia; Luo, Yishu; Xie, Tianyue; Hu, Youyang; Yan, Zhiwei; Ji, Weichao; Wang, YaXuan; Yin, Qiyou; Xian, Hua (Frontiers in Immunology, 2025)
IntroductionNeuroblastoma (NB), a malignant extracranial solid tumor originating from the sympathetic nervous system, exhibits poor prognosis in high-risk cases, with a 5-year overall survival rate below 50%. Glycolysis has been implicated in NB pathogenesis, and targeting glycolysis-related pathways shows therapeutic potential. This study investigates the role of the glycolysis-associated gene ALDOC in NB pathogenesis and its impact on chemotherapy sensitivity.MethodsTranscriptomic data from NB patients were analyzed to identify ALDOC as an independent risk factor for high-risk NB. Protein expression levels of ALDOC were assessed in NB cells versus normal cells using immunoblotting. Functional experiments, including proliferation and migration assays, were conducted in ALDOC-interfered NB cell lines. Glycolytic activity was evaluated by measuring glucose uptake, lactate production, and ATP generation. Additionally, the sensitivity of ALDOC-downregulated NB cells to cisplatin and cyclophosphamide was tested to explore its role in chemotherapy response.ResultsALDOC was identified as a high-risk prognostic marker in NB, with elevated protein expression in NB cells compared to normal controls. Silencing ALDOC significantly inhibited NB cell proliferation and migration. Glycolytic activity was markedly reduced in ALDOC-downregulated cells, evidenced by decreased glucose uptake, lactate production, and ATP levels. Furthermore, ALDOC suppression enhanced NB cell sensitivity to cisplatin and cyclophosphamide, suggesting a glycolysis-dependent mechanism underlying chemotherapy resistance.DiscussionOur findings highlight ALDOC as a critical driver of NB progression through glycolysis acceleration, with implications for therapeutic targeting. The observed increase in chemotherapy sensitivity upon ALDOC inhibition underscores its potential as a biomarker for treatment optimization. However, the complexity of glycolysis regulation, involving multiple genes and pathways, necessitates further mechanistic studies to clarify ALDOC’s specific role. Despite this limitation, our work emphasizes the importance of aerobic glycolysis in NB pathogenesis and provides a foundation for developing novel therapeutic strategies targeting ALDOC or associated pathways. Future research should explore interactions between ALDOC and other glycolytic regulators to refine combinatorial treatment approaches.